Design and implementation of multifunctional green induction lamp. (August 2020) - Zhang, Changyong; Yang, Lixin; Tan, Lang; Bai, Zhihua; Liu, Sheng
Abstract: In order to meet the needs of society for energy-saving lamps, save energy and reduce costs, this paper designed a multi-function green sensor lamp. The system is based on microcomputer, using LED lighting technology, human body infrared sensing principle, photosensitive sensor principle and acoustic sensor principle to realize a new intelligent lighting tool for automatic control of light source lighting. The intelligent control of the illumination duration from both hardware and software enables the light control and voice-activated illumination functions, and has an anti-theft function, which can effectively improve home safety.